RITUAL AQIQAH DI DESA KALEMANDALLE KECAMATAN BAJENG BARAT KABUPATEN GOWA (TINJAUAN DAKWAH KULTURAL) - Munadiyah, Munadiyah; Hasaruddin, Hasaruddin (Jurnal Berita Sosial, 2019)
<span style="font-size: 11.0pt; font-family: 'Garamond',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN">Aqiqah Ritual in Kalemandalle Village, West Bajeng Subdistrict, Gowa Regency has several series outside of the aqiqah implementation that should be, so research This aims to determine the process of the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency and to know the Da'wah message in the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency. The results of this study indicate that there are five aqiqah implementation processes in Kalemandalle Village, namely, slaughtering goats, Barzanji, giving names, cutting children's hair and providing jajjakkang. As for those containing the message of da'wah in the implementation of aqiqah there are three processes namely, slaughtering goats, cutting hair, and giving names. All three processes are recommendations of the Prophet Muhammad. As for the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency, which is merely a tradition, does not contain the message of preaching, but is only limited to customary messages. Aqiqah Ritual in Kalemandalle Village, West Bajeng Subdistrict, Gowa Regency has several series outside of the aqiqah implementation that should be, so research This aims to determine the process of the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency and to know the Da'wah message in the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency. The results of this study indicate that there are five aqiqah implementation processes in Kalemandalle Village, namely, slaughtering goats, Barzanji, giving names, cutting children's hair and providing jajjakkang. As for those containing the message of da'wah in the implementation of aqiqah there are three processes namely, slaughtering goats, cutting hair, and giving names. All three processes are recommendations of the Prophet Muhammad. As for the implementation of aqiqah in Kalemandalle Village, West Bajeng District, Gowa Regency, which is merely a tradition, does not contain the message of preaching, but is only limited to customary messages.